An exploration of challenges affecting the Adoption of Information and communication Technologies (ICTs) by Government libraries in Kenya. - Ouma, Cary, Francis (My University, 2022)
In Kenya, many libraries have embraced the use of ICTs to leverage their services. While the extent of the use of ICTs in these libraries vary vastly, it is reported in literature that the use of these technologies are also faced by different challenges. Accordingly, this study sought to the key challenges affecting the adoption of ICTs by government libraries in Kenya under two objectives: to describe the challenges affecting the adoption of ICTs by government libraries in Kenya and recommend measures that should be taken to arrest the challenges. The study was informed by e-readiness model and guided by qualitative research methods. Twelve (12) libraries were selected purposively. Data was collected from the heads of selected libraries using interview method. Website and documentary analysis was also used to enhance data quality. Data presentation and analysis was done qualitatively, however this was simplified using figures and tables based on excel software. According to the findings, the adoption of ICTs by government libraries is affected by different managerial, financial, technological and staff related challenges. Based on these findings, the study recommended the formation of ICT committee at the department of government Library Services (GLS), enhancing internet access in libraries, adapting a standard system for government libraries, development of ICT policy for libraries and exploring alternative sources of funding by libraries
Keywords: Communication; government libraries; information; Libraries; technology